Use of flow diverters in the treatment of unruptured saccular aneurysms of the anterior cerebral artery - Bhogal, Pervinder; Bäzner, Hansjörg (Journal of neuroInterventional surgery, 2017)
Background: Few publications have dealt exclusively with the use of flow diverter stents for the treatment of aneurysms of the anterior cerebral artery (ACA). Objective: To determine the efficacy of flow-diverting stents in the treatment of small, unruptured aneurysms of the ACA. Methods: We retrospectively reviewed our database of prospectively collected information for all patients treated with flow diversion for an unruptured saccular aneurysm of the ACA between September 2009 and July 2016. The aneurysm fundus size, neck size, number and type of flow-diverting stent (FDS), complications, and follow-up data were recorded. Results: In total 26 patients, with 27 aneurysms were identified that matched our inclusion criteria (11 male and 15 female). The average age of the patients was 59.3 years (range 27-77 years). All patients, except one, had a single aneurysm affecting the ACA. Fourteen aneurysms were located on the left (51.9%). The average aneurysm fundus size was 2.9 mm (range 2-6 mm). Twenty patients had follow-up angiographic studies. In total, 16 aneurysms were completely excluded, 1 aneurysm showed a very small remnant, and no follow-up angiographic data are available for the remaining patients. One patient had a treatment-related complication. Conclusions: Treatment of aneurysms arising from the ACA with flow diverters is technically feasible and carries a high degree of success with low complication rate.